Análisis de un sistema de seguridad basado en el internet de las cosas para viviendas urbanas. - Saa Ayala, Juan Fernando (2023)
The Internet of Things (IoT) has become an integral part of our daily lives, and it is expanding even more as the number of smart devices increases. This poses a number of security challenges as IoT devices connect to the network and share data. To address these challenges, a team of researchers developed an IoT-based security system for urban homes. The system uses wireless sensors to collect data and store it in the cloud. In addition, a wireless data communication network is used to transmit data from the sensors to a remote control center. The system includes an alert system that can be configured to send alerts to the user if any type of anomalous activity is detected. The system also includes an authentication mechanism to ensure that only authorized users can access the data. Finally, the system provides a user interface so that users can interact with the system. In conclusion, this security system for urban homes with IoT is an effective solution to improve security in domestic environments. The objective of this analysis is to develop a security system for urban homes connected to the Internet of Things (IoT). The security system will consist of a variety of devices connected to the IoT network, such as motion sensors, video surveillance cameras, smoke and CO presence sensors, intrusion detectors, alarm systems, etc. These devices will be connected to a cloud platform that will be configured to receive notifications in case any anomalous event is detected. The platform will have an authentication system to provide adequate security and users will be allowed to access the devices from anywhere. The system will also be designed to check the integrity of connected devices, provide automatic firmware updates, and allow users to control access to their devices. A mobile app will be included to allow users to remotely configure and control the devices.